Strategi Pengembangan Sumber Daya Manusia untuk Meningkatkan Kualitas Kerja - Najwaturrohmah Najwaturrohmah; Gina Mardiah Putri R.; Zahra Nur Afni; Sri Mulyeni (Jurnal Pemimpin Bisnis Inovatif, 2026)
In the dynamic era of information technology disruption and globalization, organizations face increasingly fierce competition. High-quality human resources (HR) represent the core strength for organizations to survive and compete, demanding well-designed development strategies. This study aims to comprehensively analyze various effective HR development strategies to enhance work quality, productivity, and operational efficiency across various organizational sectors. The method employed in this research is a literature study (library research). Data collection was conducted by deeply reviewing ,and analyzing, sourced from various online publications. The results indicate that HR development strategies in the corporate sector are effectively realized through a combination of regular technical training, employee rotation policies, and KPI-based coaching and mentoring programs to implement the principle of "the right man in the right place". In the public and government sectors, the implementation of functional education and training is proven to optimize the quality of public services, despite facing constraints of limited budget and personnel. Meanwhile, within the local economic scope, the competitiveness of MSMEs and regional tourism is successfully accelerated through managerial training, marketing digitalization, and adherence to standard operating procedures (SOP). This study concludes that modern organizational resilience depends on a paradigm shift toward a human-centric management approach. Organizations need to evaluate budget imbalances favoring physical development to harmoniously synergize with the sustainable development of human talent's competence, creativity, and digital literacy.